Implementasi Aspek Afektif: Upaya Guru dalam Menginternalisasikan Nilai Sopan Santun Pada Siswa di MA Ma’arif Al-Mukarrom Kauman Ponorogo - Hanifah Tri Handayani; Nurul Malikah; Hamdan Syukril Imama; Hasna' Afifah Dawama; Ikhwanuddin Ikhwanuddin; Ikmal Nur Azizi; Irin Putri Setiani (https://ejournal.insuriponorogo.ac.id/, 2024)
This research is motivated by observation data showing teachers' efforts in the affective domain towards internalizing politeness values ​​at MA Ma'Arif Al-Mukarrom. To respond to this, the researcher conducted an environmental action research in the Madrasah which aims to determine efforts in internalizing politeness values. This research uses a descriptive qualitative method which aims to understand the phenomena that exist in Madrasah AL-Mukarom. Data collection for this research uses interview and observation techniques. The objectives to be achieved in this research include: (1) Knowing efforts to internalize politeness values ​​in students, (2) Knowing the increase in the results of implementing the affective domain of internalizing politeness values. This research was conducted in the Madrasah Al-Mukarrom environment. This research measures the affective domain, especially in internalizing politeness values. In its implementation, there are several implementation processes, including; 1) Implementing the 5S culture, in the Madrasah Al-Mukarom environment and has implemented including; a) Greetings and shaking hands between students and educators in front of the Madrasah. b) Giving a smile when passing by. c) Greeting when meeting in class with, from the three applications, it functions to instill student character. 2) Implementing the habit of praying Dhuha and Dhuhur in congregation, which is expected to instill the values ​​of togetherness and solidarity among students. 3) Implementing the habit of reading the Quran, which is expected to increase their love and deepen their understanding of Islamic teachings. From the research data, it is recommended to teachers to further implement the values ​​of politeness in the Madrasah Al-Mukarrom environment.